البوابات في الخانات العثمانية لمدينة حلب القديمة ( أنواعها وعناصرها المعمارية) - طعمه أنيت (Latakia University Journal -Engineering Sciences Series, 2019)
Khans constitute one of the most important buildings throughout history, because of their important role in the economic life. They were marked by the enormity of construction, area, and also by details and architectural elements either in the unique forms of gates, the interior spaces, courtyards and openings internal windows and doors. Khans gates formed unique architectural panels of beauty and richness by their decoration. They formed an important subject worthy of studying and research. Khans flourished significantly as Aleppo was one of the most important commercial cities throughout history, because of its important geographical location, something which distinguished it from other cities., especially during the Ottoman era, which saw the construction of more than fifty Khans inside the city. These khans were established during different periods of the Ottoman era, which seem similar in the general plan, but different in details depending on the period of construction. This resulted in different models with different details, as reflected in the varied forms of gates in size, decoration and architectural details. Khan gates in the sixteenth and seventeenth centuries were marked by the big dimension, the intensity of motifs, and rich architectural details influenced clearly by the Mamluk architecture. In comparison, during the eighteenth and nineteenth centuries seemed more simple, less massive than its predecessors, and even devoid of decoration. The effects of European architecture were clear on the gates of Khans in the end of the Ottoman era in the early twentieth century. As a result, khans gates in Aleppo during the Ottoman era waere characterized by diversity in size, configuration and architectural details, which must be recognized in any restoration project, in order to preserve the original features and the characteristic of these monuments. تشكل الخانات واحدة من أهم المباني عبر التاريخ نظراً للدور الهام الذي لعبته في الحياة الاقتصادية, وقد تميّزت بضخامة بنائها ومساحاتها, كما تميّزت بالتفاصيل والعناصر المعمارية المتنوعة سواء من حيث البوابات وأشكالها الفريدة, أو من حيث الفراغات الداخلية والأفنية والفتحات الداخلية كالنوافذ والأبواب. وقد شكلت البوابات الخارجية للخانات لوحات معمارية فريدة بجمالها وغنى مفرداتها وزخرفتها, لذا شكلت موضوعاً هاماً يستحق الدراسة والبحث. ولمّا كانت حلب من أهم المدن التجارية عبر التاريخ, حيث جعلها موقعها الجغرافي الهام تلعب دورا محورياً في الحركة التجارية العالمية عبر العصور, هذا الأمر الذي ميّزها عن سواها من المدن فازدهرت عمارة الخانات فيها بشكل ملحوظ وانتشرت بكثافة خاصة خلال العصر العثماني الذي شهد بناء ما يزيد عن خمسين خاناً داخل المدينة, أنشئت خلال فترات مختلفة من العصر العثماني, وقد تشابهت من حيث المخطط العام بينما اختلفت تفاصيلها تبعاً للفترة الزمنية التي شيّدت فيها كل منها, مما أفرز نماذج مختلفة من حيث التفاصيل والتي انعكست بدورها على البوابات الرئيسية التي اختلفت أشكالها وتنوعت سواء من حيث الحجم والتشكيل أو من حيث الزخرفة والتفاصيل المعمارية. حيث تميّزت خانات القرنين السادس عشر والسابع عشر بالضخامة وكثافة الزخارف وغنى التفاصيل المعمارية متأثرة بالعمارة المملوكية بشكل واضح, بينما بدت بوابات الخانات خلال القرنين الثامن عشر والتاسع عشر بسيطة وأقل ضخامة من سابقاتها كما أنها خالية من الزخارف, في حين يظهر التأثر بالعمارة الأوروبية الوافدة واضحاً في بوابات الخانات خلال نهاية العصر العثماني في مطلع القرن العشرين. وكنتيجة لما سبق نجد أنّ بوابات الخانات في حلب خلال العصر العثماني تميّزت بالتنوع من حيث الحجم والتكوين والتفاصيل المعمارية, الأمر الذي لابد من التنبه له ودراسته عند القيام بأي عمل ترميم أو صيانة وذلك بهدف الحفاظ على الملامح الأصيلة والهوية المميزة لهذه الأوابد.